Monkeypox virus infection of rhesus macaques induces massive expansion of natural killer cells but suppresses natural killer cell functions. - Haifeng Song; Nicole Josleyn; Krisztina Janosko; Jeff Skinner; R Keith Reeves; Melanie Cohen; Catherine Jett; Reed Johnson; Joseph E Blaney; Laura Bollinger; Gerald Jennings; Peter B Jahrling (PLoS ONE, 2013)
Natural killer (NK) cells play critical roles in innate immunity and in bridging innate and adaptive immune responses against viral infection. However, the response of NK cells to monkeypox virus (MPXV) infection is not well characterized. In this intravenous challenge study of MPXV infection in rhesus macaques (Macaca mulatta), we analyzed blood and lymph node NK cell changes in absolute cell numbers, cell proliferation, chemokine receptor expression, and cellular functions. Our results showed that the absolute number of total NK cells in the blood increased in response to MPXV infection at a magnitude of 23-fold, manifested by increases in CD56+, CD16+, CD16-CD56- double negative, and CD16+CD56+ double positive NK cell subsets. Similarly, the frequency and NK cell numbers in the lymph nodes also largely increased with the total NK cell number increasing 46.1-fold. NK cells both in the blood and lymph nodes massively proliferated in response to MPXV infection as measured by Ki67 expression. Chemokine receptor analysis revealed reduced expression of CXCR3, CCR7, and CCR6 on NK cells at early time points (days 2 and 4 after virus inoculation), followed by an increased expression of CXCR3 and CCR5 at later time points (days 7-8) of infection. In addition, MPXV infection impaired NK cell degranulation and ablated secretion of interferon-γ and tumor necrosis factor-α. Our data suggest a dynamic model by which NK cells respond to MPXV infection of rhesus macaques. Upon virus infection, NK cells proliferated robustly, resulting in massive increases in NK cell numbers. However, the migrating capacity of NK cells to tissues at early time points might be reduced, and the functions of cytotoxicity and cytokine secretion were largely compromised. Collectively, the data may explain, at least partially, the pathogenesis of MPXV infection in rhesus macaques.